2009
DOI: 10.1111/j.1447-0349.2009.00622.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in self‐reported anxiety in rural adolescents

Abstract: An anxiety disorder affects 13 out of every 100 children. The purpose of this paper is to determine if there are differences in self-reported anxiety between male and female rural adolescents. One hundred and ninety three students aged 14-17 years in three western Pennsylvania rural high schools, USA, were surveyed. The majority of participants were Caucasian (86.5%, n = 167), female (53.4%, n = 103), and aged 15.57 (SD = .93). Females' mean self-reported anxiety score was higher than the males' score (p < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…However, a larger study or splitting the participant group along a gender continuum may have revealed a significant difference. This data is in line with other gender-based anxiety studies (Puskar et al, 2009), where females reported higher levels of anxiety than males. It has been suggested that females may be more inclined to reveal a true record of their feelings, whereas males may suppress their reporting as befitting of their burgeoning masculinity.…”
Section: Mastery Experiencesupporting
confidence: 93%
“…However, a larger study or splitting the participant group along a gender continuum may have revealed a significant difference. This data is in line with other gender-based anxiety studies (Puskar et al, 2009), where females reported higher levels of anxiety than males. It has been suggested that females may be more inclined to reveal a true record of their feelings, whereas males may suppress their reporting as befitting of their burgeoning masculinity.…”
Section: Mastery Experiencesupporting
confidence: 93%
“… 27 , 28 However, the child’s age and developmental level are considered important factors that influence the anxiety levels between sexes. Puskar et al, 31 in their study of 193 adolescents aged 14-17 years demonstrated that females’ mean self-reported anxiety score was significantly higher than their male counterparts. Conversely, there was no difference in anxiety levels between 252 girls and boys aged 5-10 years attending a dental hospital.…”
Section: Discussionmentioning
confidence: 95%
“…The sample consisted of 193 students age 14–18 years ( M = 15.57, SD = 0.93) from three public high schools in rural southwestern Pennsylvania who were enrolled in a randomized‐controlled intervention study. Findings from the intervention study have been published elsewhere (Puskar, Bernardo, Ren, Stark, & Lester, 2009; Puskar & Grabiak, 2008; Puskar, Ren, Bernardo, Haley, & Stark, 2008). The participants were recruited from the 9th, 10th, and 11th grades.…”
Section: Methodsmentioning
confidence: 99%